Abundant intracellular IgG in enterocytes and endoderm lacking FcRn. - Sudhasri Mohanty; Jonghan Kim; Latha P Ganesan; Gary S Phillips; John M Robinson; Clark L Anderson (PLoS ONE)
FcRn, a non-classical MHCI molecule, transports IgG from mother to young and regulates the rate of IgG degradation throughout life. Brambell proposed a mechanism that unified these two functions, saying that IgG was pinocytosed nonspecifically by the cell into an FcRn-expressing endosome, where, at low pH, it bound to FcRn and was exocytosed. This theory was immediately challenged by claims that FcRn specificity for ligand could be conferred at the cell surface in neonatal jejunum. Assessing Brambell's hypothesis we found abundant nonspecifically endocytosed IgG present in the cytoplasm of FcRn(-/-) enterocytes. Further, IgG was present in the intercellular clefts and the cores of FcRn(+/+) but not FcRn(-/-) jejunum. FcRn specificity for ligand could be determined within the cell.